A negociação coletiva trabalhista e a intervenção mínima do estado - Duarte, Luiz Filipe (2019)
This work analyzes the interventionist role of the State in collective bargaining. It is questioned, as problem, the possibility of minimal State interference in the negotiation process to enable a system in which labor relations reflect the free will of the parties involved, surpassing the institute, as hypothesis, the figure of mere complementary instrument of adequacy of the imposed norm, from a model endowed with greater aptitude to adapt to the flexibility of the market. To do so, the collective labor negotiation itself, its origin and evolution, its principles and main functions are outlined, as well as the procedures that are part of the regulatory framework of Labor Law. Then, the role of the State is analyzed regarding its interdependence with not only social issues, but also political and, above all, economic ones. It deals with the evolution of the State and its interventionist role in the economy and its relation with employment and labor issues, mainly in collective bargaining, considering freedom of association issues, the regulatory power of Labor Justice and as to the constitutional right to negotiation as a fundamental right. Recent changes in labor legislation carried out by Law n. 13.467/2017 are also approached, highlighting, among other legislator goals, the wish to improve labor relations in Brazil through the valorization of collective bargaining between workers and employers. Finally, after outlining the role of collective bargaining in the current socio-economic reality, the application of the principle of subsidiarity as a parameter for the State to act, as well as the defense of constitutionality of the Law which provides for minimum state intervention in collective bargaining, it can be concluded, in response to the problem, that this is the way the State should promote collective bargaining, without any disrespect to freedom of the parties neither their willingness to negotiate.